Haplotype analysis suggest common founders in carriers of the recurrent BRCA2 mutation, 3398delAAAAG, in French Canadian hereditary breast and/ovarian cancer families - Foulkes William D; Mes-Masso; Shen Zhen; Perret Chantal; Arcand Suzanna L; Leblanc Guy; Oros Kathleen K; Ghadirian Parviz; Provencher Diane; Tonin Patricia N (BMC, 2006)
Abstract Background The 3398delAAAAG mutation in BRCA2 was recently found to recur in breast and/or ovarian cancer families from the French Canadian population of Quebec, a population that has genetic attributes consistent with a founder effect. To characterize the contribution of this mutation in this population, this study established the frequency of this mutation in breast and ovarian cancer cases unselected for family history of cancer, and determined if mutation carriers shared a common ancestry. Methods The frequency was estimated by assaying the mutation in series of French Canadian breast cancer cases diagnosed before age 41 (n = 60) or 80 (n = 127) years of age, and ovarian cancer cases (n = 80) unselected for family history of cancer by mutation analysis. Haplotype analysis was performed to determine if mutation carriers shared a common ancestry. Members from 11 families were analyzed using six polymorphic microsatellite markers (cen-D13S260-D13S1699-D13S1698-D13S1697-D13S1701-D13S171-tel) spanning approximately a 3.6 cM interval at the chromosomal region 13q13.1, which contains BRCA2. Allele frequencies were estimated by genotyping 47 unaffected female individuals derived from the same population. Haplotype reconstruction of unaffected individuals was performed using the program PHASE. Results The recurrent BRCA2 mutation occurred in 1 of 60 (1.7%) women diagnosed with breast cancer before 41 years of age and one of 80 (1.3%) women with ovarian cancer. No mutation carriers were identified in the series of breast cancer cases diagnosed before age 80. Mutation carriers harboured one of two haplotypes, 7-3-9-3 - [3/4]-7, that varied with marker D13S1701 and which occurred at a frequency of 0.001. The genetic analysis of D13S1695, a polymorphic marker located approximately 0.3 cM distal to D13S171, did not favour a genetic recombination event to account for the differences in D13S1701 alleles within the haplotype. Although mutation carriers harbour genotypes that are frequent in the French Canadian population, neither mutation-associated haplotype was plausible in reconstructed haplotypes of 47 individuals of French Canadian descent. Conclusion These results suggest that mutation carriers share a related ancestry; further supporting the concept that recurrent BRCA1 and BRCA2 mutations in the French Canadian population could be attributed to common founders. This finding provides further support for targeted screening of recurrent mutations in this population before large-scale mutation analyses are performed.